Obesity and ABO blood group: Is there an association?. (June 2020) - Flor, Cristina Rabelo; Gomes Moura, Isabel Cristina; Baldoni, André Oliveira; Loureiro, Paula; Teixeira, Carolina Miranda; Carneiro-Proietti, Anna Bárbara; Oikawa, Marcio Katsumi; de Almeida Neto, Cesar; Witkin, Steven S.; Sabino, Ester Cerdeira; Oliveira, Cláudia Di Lorenzo
Abstract: Objective: We evaluated the association between obesity and ABO blood group antigens in a large sample of blood donors. Methods: This cross-sectional study included 549, 690 individuals who donated blood at three blood donation centers in Brazil between 2006 and 2012. Subjects were categorized by body mass index (BMI) as normal weight, overweight and obese. A multivariate analysis was performed by Ordinal Logistic Regression to evaluate associations between BMI and ABO blood group by gender and age. Results: Among the participants 37% were overweight and 15.3% were obese. The majority of participants were male (65.4%), less than 44 years old (86.6%) and had greater than 11 years of education (61.4%). Blood group O had the highest prevalence (48.9%) and group AB had the lowest prevalence (3.7%) among participants. The mean BMI was slightly above 25 kg/m 2, the lower limit of an overweight classification in all ABO blood groups. Associations between specific ABO antigens and BMI were identified that differed according to gender. The O and B blood groups were associated with a greater prevalence of obesity in women and a lower prevalence in men. Conclusions: Carriage of specific alleles in the ABO blood group may differently influence BMI, according to gender. Highlights: Some ABO blood group may differently influence BMI, according to gender. For women, blood types B and O was associated with a greater prevalence of obesity. For men, the O and B blood groups were associated with a decreased prevalence of obesity. Blood type and BMI was associated only in some age groups.